A regional assessment of land‐based carbon mitigation potentials: Bioenergy, BECCS, reforestation, and forest management. Issue 5 (1st April 2020) - Krause, Andreas; Knoke, Thomas; Rammig, Anja
Abstract: Land‐based solutions are indispensable features of most climate mitigation scenarios. Here we conduct a novel cross‐sectoral assessment of regional carbon mitigation potential by running an ecosystem model with an explicit representation of forest structure and climate impacts for Bavaria, Germany, as a case study. We drive the model with four high‐resolution climate projections (EURO‐CORDEX) for the representative concentration pathway RCP4.5 and present‐day land‐cover from three satellite‐derived datasets (CORINE, ESA‐CCI, MODIS) and identify total mitigation potential by not only accounting for carbon storage but also material and energy substitution effects. The model represents the current state in Bavaria adequately, with a simulated forest biomass 12.9 ± 0.4% lower than data from national forest inventories. Future land‐use changes according to two ambitious land‐use harmonization scenarios (SSP1xRCP2.6, SSP4xRCP3.4) achieve a mitigation of 206 and 247 Mt C (2015–2100 period) via reforestation and the cultivation and burning of dedicated bioenergy crops, partly combined with carbon capture and storage. Sensitivity simulations suggest that converting croplands or pastures to bioenergy plantations could deliver a carbon mitigation of 40.9 and 37.7 kg C/m 2, respectively, by the year 2100 if used to replace carbon‐intensive energy systems and combined with CCS. However, under less optimistic assumptions (including no CCS), only 15.3 and 12.2 kg C/m 2 are mitigated and reforestation might be the better option (20.0 and 16.8 kg C/m 2 ). Mitigation potential in existing forests is limited (converting coniferous into mixed forests, nitrogen fertilization) or even negative (suspending wood harvest) due to decreased carbon storage in product pools and associated substitution effects. Our simulations provide guidelines to policy makers, farmers, foresters, and private forest owners for sustainable and climate‐benefitting ecosystem management in temperate regions. They also emphasize the importance of the CCS technology which is regarded critically by many people, making its implementation in the short or medium term currently doubtable. Abstract : We here assess regional carbon mitigation potentials for a range of land management options by performing simulations with an ecosystem model under climate change. Reforestation on agricultural land yields larger carbon mitigation potentials than the cultivation of bioenergy crops in the absence of the carbon capture and storage technology. Alternative forest management techniques offer only limited prospects, emphasizing the need for rapid emission reductions.